Determination of Auditors' Ethical Perception and Individual Morality as Intervening Variables - Hermawan, Sigit; Imania, Salsa Billa Rahma; Rahayu, Duwi; Biduri, Sarwendah; Rahayu, Ruci Arizanda (Jurnal Ilmiah Akuntansi dan Bisnis, 2023)
Auditors’ ethical perception is influenced by both positive and negative factors. This research aimed to obtain the empirical evidence related to the influence of love of money, Machiavellianism, and religiosity, on auditors' ethical perception and individual morality as intervening variables. The research involved 14 public accounting firms with 65 auditors selected as the research samples obtained using a purposive sampling technique. The collected data were then analyzed using Partial Least Square Structural Equation Modeling (PLS SEM). The research results showed that love of money, Machiavellianism, and religiosity influenced the auditor's ethical perception and individual morality. However, individual morality could not be considered as the intervening variable in this research. Based on the research results, public accounting firms had proven that auditors' ethical perception and individual morality could be improved by reducing love of money, eliminating Machiavellianism, and increasing religiosity belonging to the auditors. Keywords:  love of money, machiavellian nature, religiosity, individual morality, ethical perception